Investigating the Impact of Social Capital on Performance in Mehr-Eqtesad Banks from Employee's Perspective - belghis bavarsad; farajallah rahimi; adeleh salimifard; mohammadhossein ghalambor (توسعه اجتماعی, 2017)
Since developing countries are becoming service community and within a dynamic environment established by increasing competition, globalization, the emergence of new technologies, the way to growth, the achievement of high performance and survival in the global economy is innovation. Also, the success of today's organizations cannot only be evaluated in the accumulation of material wealth, physical facilities and equipment to the latest information and communication technologies. Since financial physical and human capital without social capital, lack effective performance. The present study aims to investigate the influence of social capital on the financial performance of the Mehr-Eqtesad Banks. The population consisted of 315 managers and employees of the bank in Khuzestan province which 170 samples were determined according to Morgan table. 241 questionnaires were distributed between employees, of which 155 completed questionnaires were Analysis. Given the nature of the study and the examination of the causal hypothesis, we used structural equation modelling, PLS, and SPSS. Results revealed that social capital has significant positive effect on service employee commitment and innovation orientation. But social capital has no positive impact on financial performance. Moreover, service employee commitment, innovation orientation and significantly affect financial performance.